Creative Practice as a Catalyst for Developing Connectedness Capabilities: A Community Building Framework from the Teaching International Students Project - Snepvangers, Kim; Rourke, Arianne (Journal of International Students, 2020)
Focusing on a section of the Teaching International Students (TIS) project this article captures student and mentor perspectives within a Project-Based Professional Experience (PBPE) in the context of a large research-intensive university in Sydney, Australia. Animations co-produced with students were part of a Work Integrated Learning (WIL) compulsory upper-level course, leading to a ‘Community Building Framework’. The research goal shifted the educational purpose from didactic physical placements to collaborative dynamics where students, including international students, staff, and industry perspectives were ‘valued’. Prioritizing intercultural learning ‘challenged’ contested attitudes and ‘built’ communities of practice in a workforce focused ecology. Findings emerged from reflective interchanges whilst working iteratively and collaboratively with students, to inform the PBPE online framework.